Is There an Association Between Schizophrenia and Sexual Dysfunction in Both Sexes? A Systematic Review and Meta-Analysis - Zhao, Shankun; Wang, Xiaolan; Qiang, Xie; Wang, Hui; He, Jian; Shen, Maolei; Zheng, Changjun; Kang, Ran (Journal of sexual medicine, 2020)
Mounting clinical studies have reported patients with schizophrenia are at high risk of developing sexual dysfunction (SD), but a directly calculated prevalence of SD is currently lacking. To further quantify the association between schizophrenia and SD. MEDLINE (PubMed), Embase (OVID), the Cochrane Library databases, and the PsycINFO were systematically searched for eligible studies reporting the sexual functioning in patients with schizophrenia. This meta-analysis has been registered on PROSPERO (ID: CRD42019121720, http://www.crd.york.ac.uk/PROSPERO). The relationship between schizophrenia and SD was detected by calculating the relative risk (RR) with a 95% confidence interval (CI). The GRADE-profiler was employed to rank the quality of the evidence. 10 observational studies (3 case-control studies and 7 cross-sectional studies) were finally included, enrolling a total of 3,570 participants (mean age 28.6–46.2 years), of whom 1,161 had schizophrenia and the remainders were the healthy control subjects. Synthetic results indicated that schizophrenia was significantly associated with an increased risk of SD regardless of gender (3 studies reporting both sexes: RR = 2.24, 95%CI: 1.66–3.03, P < .001, heterogeneity: I2 = 0.0%, P = .431; 7 studies reporting men: RR = 2.63, 95%CI: 1.68–4.13, P < .001, heterogeneity: I2 = 82.7%, P < .001; 5 studies reporting women: RR = 2.07, 95%CI: 1.46–2.94, P < .001; heterogeneity: I2 = 79.7%, P = .001). In accordance with the GRADE-profiler, the quality of the evidence of primary outcomes was LOW, MODERATE, and LOW in studies including both sexes, men, and women, respectively. Our findings confirmed the potential link between schizophrenia and SD. Clinicians should routinely assess the sexual functioning for those patients with schizophrenia and further recommend the preferred antipsychotics for them. This is the first meta-analysis investigating the association between schizophrenia and the risks of SD in both sexes. Nonetheless, substantial heterogeneities were identified across the selected studies. Robust data from this meta-analysis showed increased rates of SD in patients with schizophrenia compared with the general populations. Therefore, more specific psychological and pharmaceutical interventions are needed to help patients with schizophrenia gain a better sexual life. Zhao S, Wang X, Qiang X, et al. Is There an Association Between Schizophrenia and Sexual Dysfunction in Both Sexes? A Systematic Review and Meta-Analysis. J Sex Med 2020;17:1476–1488.